4 Elements in the ESL/EFL Classroom: a Teacher’s Handbook of Activities - Shkola, Irуna; Saliuk, Bohdana; Shevchenko, Maryna (Житомир: Видавець ПП “Євро-Волинь”, 2024)
In the dynamic realm of language teaching, the manual “4 Elements in the ESL/EFL Classroom: a Teacher’s Handbook of Activities” emerges as a collaborative effort by a team of dedicated authors – Irуna Shkola, Bohdana Saliuk, and Maryna Shevchenko. Tailored for both in-service and pre-service English teachers and aspiring educators in the field of English language and foreign literature, this guide focuses on the essential language skills: listening, reading, writing, and speaking. It corresponds to the context of the innovative model of training of pre-service English language teachers, “New Generation School Teachers,” developed in cooperation with the British Council in Ukraine and the Ministry of Education and Science of Ukraine. It can be used during the implementation of the module “Teaching listening, reading, writing, speaking in English” of the educational component “Methods of teaching the subject (English language and foreign literature)”. What sets this handbook apart is its innovative approach, where each language activity is associated with one of the four natural elements – fire, air, water, and earth. The meticulously crafted structure of the manual provides clear instructions, learning objectives, and versatile options, including the integration of digital technologies. This not only facilitates the creation of engaging and diverse English lessons but also streamlines the teacher’s preparation time. It’s worth noting that the activities presented in this book are not tied to specific topics, offering educators the flexibility to implement them across various subjects. Furthermore, each activity comes with additional variations to accommodate students’ language proficiency levels or to target the development of different language skills.
4 елементи на уроці англійської мови: посібник активностей для вчителя
Навчально-методичний посібник здійснює практичну підтримку модуля “Навчання аудіювання, читання, письма, говоріння англійською мовою”, що є складовою освітнього компонента “Методика навчання предмета (англійська мова і зарубіжна література)”. У посібник включено систему активностей, які розвиватимуть в учнів навички чотирьох видів мовленнєвої діяльності – аудіювання, читання, письма, говоріння, що і є тими чотирма елементами на уроці англійської мови. Кожна активність підкріплена цифровими інструментами, використання яких уможливлює інтерактивне навчання, індивідуальний підхід у навчанні, створює динамічне і ефективне освітнє середовище. Для вчителів-практиків і здобувачів вищої освіти, які навчаються на спеціальності 014 Середня освіта, спеціалізації 014.021 Англійська мова та зарубіжна література.
Keywords: language aquisition; activities; teaching English; listening; reading; writing; and speaking